2021
DOI: 10.1017/s1366728921000699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of language mixing on bilingual children's word learning

Abstract: Language mixing is common in bilingual children's learning environments. Here, we investigated effects of language mixing on children's learning of new words. We tested two groups of 3-year-old bilinguals: French–English (Experiment 1) and Spanish–English (Experiment 2). Children were taught two novel words, one in single-language sentences (“Look! Do you see the dog on the teelo?”) and one in mixed-language sentences with a mid-sentence language switch (“Look! Do you see the chien/perro on the walem?”). Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…We did not observe a difference in data loss between the two coding methods. Jardak, et al, 2021), further supporting this approach.…”
Section: Codingmentioning
confidence: 56%
See 3 more Smart Citations
“…We did not observe a difference in data loss between the two coding methods. Jardak, et al, 2021), further supporting this approach.…”
Section: Codingmentioning
confidence: 56%
“…one study suggested that Spanish-English children may have slightly weaker skills in real-time language tasks than French-English children (Byers-Heinlein, Jardak, et al, 2021). Following the functional account, if some children were slower to switch between processing their two languages, or if they were less aware of its meaning, it is possible that they were able to "listen through" the uninformative adjective more easily (or under a prediction-based framework, encountered little to no prediction error).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2022) done studies on best practices for measuring bilingualism; Torregrossa et al (2021) on reference use among bilingual children; Şenaydın and Dikilitaş (2022) on the relationship between bilingualism and identity in addition Gardner-Chloros (2009), Moriguchi and Kanda (2020), Soesman and Joel (2021), Tomić and Valdés (2022), Tomoschuk at al. (2021), Byers-Heinlein at al. (2022), and Broersma et al (2020 conducted studies on code switching in bilinguals.…”
Section: Introductionmentioning
confidence: 99%